Luminescence Characteristics of LaAlO3:Eu3+ Obtained by Modified Pechini’s Method - Hernández, Alfredo Morales; Alfaro, Mayra A. de León; Villatoro, Antonio Barrera; Falcony, Ciro; Montalvo, Teodoro Rivera; Medina, Juan Zarate (Scientific Research, 2017)
The aim of the present work was to investigate the luminescent properties of europium-doped lanthanum aluminate (LaAlO3) powder prepared by Modified Pechini (MP) method. Samples were prepared at different Eu3+ concentrations and calcined at 1600˚C. Structural and morphology characterizations were obtained by X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscope (TEM). Luminescent properties were analyzed by photoluminescence (PL) and thermoluminescent phenomena. The XRD pattern shows pure lanthanum aluminate oxide LaAlO3 with a rhombohedral structure. Photoluminescence studies of the powders was related to 4f → 4f( 5 D0 → 7 Fi ) (i = 1, 2, 3, 4) transitions of Eu3+ ion, the most intense emission of Eu3+ in LaAlO3 was registered for the transition 5 D0 → 7 F1, for 5% of Eu3+. The recorded TL glow curves of excited samples showed a main TL peak, the main peak appeared its maximum as a function of excitation energy. The investigation demonstrates that polycrystalline LaAlO3:Eu3+ powders calcined at 1600˚C have interesting luminescent characteristics.
Keywords: Modified Pechini Method; LaAlO3:Eu3+; Photoluminescence; Thermoluminescence